The Effect of Leadership Style and Job Satisfaction on Employee Work Discipline at the Tanah Datar Education Office - Ebit Bimas Saputra; Desmiwerita Desmiwerita (Greenation Research & Yayasan Global Resarch National, 2023)
This study aims to reveal and analyze: (1) The effect of leadership style on employee job satisfaction at the Tanah Datar Education Office, (2) The influence of leadership style and job satisfaction on employee work discipline at the Tanah Datar Education Office. This type of research is associative descriptive research. The data analysis technique used is descriptive analysis and inductive analysis using path analysis techniques with the SPSS Version 1 5.00 program. The research results show that: (1). leadership style has a significant effect on work discipline, (2). Job satisfaction has a significant effect on work discipline, ( 3 ). Leadership style And Job satisfaction have a significant effect on work discipline.